Pendampingan Penyusunan Laporan Keuangan Sederhana Berdasarkan Kaidah SAK-EMKM Bagi UMKM Agroindustri Tahu “H. Pepen” di Desa Rancaekek Kulon, Kecamatan Rancaekek, Kabupaten Bandung: Assistance in Preparing Simple Financial Statements Based on SAK-EMKM Principles for Tofu Agro-Industry MSME "H. Pepen" in Rancaekek Kulon Village, Rancaekek District, Bandung Regency - Arifin, Samsul; Rahmah, Ulya; Muthmainnah, Salma (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2026)
This community service activity focuses on assisting the preparation of simple financial reports based on SAK-EMKM for the Agroindustry SME "H. Pepen" Tofu in Bandung Regency. Although the enterprise has been operating since 1990 with relatively stable production capacity, the main challenge for the partner is the lack of a structured financial recording system in accordance with accounting standards. All business transactions are still recorded manually and unsystematically, which complicates business analysis, accurate cost of goods sold (COGS) calculations, and loan applications. The objectives of this activity are (1) to enhance financial literacy among SME actors and (2) to assist in preparing simple financial reports in compliance with SAK-EMKM. The method employed is Participatory Action Research (PAR), consisting of observation, accounting workshops, and technical assistance. The results indicate that the mentoring process successfully improved the partner's understanding of the importance of financial reporting, as evidenced by SAK-EMKM. The partner has now developed a simple financial report format (utilizing manual cash books and basic Excel templates) that can be applied independently. The service team's involvement also serves as a sustainable model of empowerment that other SMEs can replicate.